Human Capabilities and Economic Growth: A Comparative Human Capability Index - Yılmazer, Mine; Cinar, Serkan (International Journal of Economics and Financial Issues, 2015)
The purpose of this paper is to contribute to research probing the underlying role human capital plays on economic growth in 1985-2011 for 17 developed and developing countries. Firstly, we examined the determinants of human capabilities and formulated a new human capital index (Comparative Human Capability Index). Secondly, we analyzed the relationship between human capital and economic growth using the endogenous growth model. Results of the panel cointegration tests support a long-run positive relationship between human capital and economic growth in both developed and developing countries, however our results show that human capital is more effective in developed countries than in developing countries. Keywords: Human Development; Economic Growth; Panel Data JEL Classifications: C33; O15